The philosophy of private deterrence in the penal code - Abdulridha, Jaafar Naser; Abbas, Qusay Ali; Hashim, Salwan Jaber (Cuestiones Políticas, 2020)
The aim of article was to discuss the philosophy of private deterrence under Iraq’s penal code. The methodology adopted was the inductive approach, which helps to extrapolate legal texts with this study and the jurisprudence of legal jurists. The Legislator applies to the threat with punishment the harm and pain that will be inflicted on them if the crime is eaten by law, what is known as public deterrence speech. For its part, the special deterrent will be responsible for reforming the meaning and morality of the offender, following various means provided by the legislature and designing a method of education of the deprived of liberty, allowing them the voluntary work determined by the conditions of each penance conditions or even by the subsequent formal and informal reintegration mechanisms of ex-convictions. It is concluded that these methods and others can contribute significantly to the achievement of the deterrence objectives, which is to reform and evaluate the offender’s conduct according to criminal gravity on a case-by-case basis.